Multiple sclerosis in LRRK2 G2019S Parkinson’s disease and isolated nigral degeneration in a homozygous variant carrier - Wise, Adina; Ortega, Roberto A.; Raymond, Deborah; Cervera, Alessandra; Thorn, Emma; Leaver, Katherine; Russell, David S.; Bressman, Susan B.; Crary, John F.; Saunders-Pullman, Rachel (Frontiers in neurology, 2024)
variants have been associated with immune dysregulation as well as immune-related disorders such as IBD. A possible relationship between multiple sclerosis (MS) and PD has also been suggested. Further, neuropathologic studies of homozygous G2019S carriers with Parkinson's disease (PD) are rare, and there are no systematic reports of clinical features in those cases. We investigated the co-occurrence of PD and MS in our research cohort and report on two cases of MS in PD as well as neuropathological findings for one. MS preceded PD in 1.4% (2/138) of participants with G2019S variants, and in none (0/638) with idiopathic PD ( = 0.03). One case with MS and PD was a G2019S homozygous carrier, and neuropathology showed evidence of substantia nigra pars compacta degeneration and pallor without Lewy deposition, as well as multiple white matter lesions consistent with MS-related demyelination. The increased prevalence of MS in PD further supports an important role for immune function for PD. This co-occurrence, while rare, suggests that MS may be an expression of the G2019S variant that includes both MS and PD, with MS predating features diagnostic of PD. The neuropathology suggests that the MS-related effects occurred independent of synuclein deposition. Importantly, and in addition, the neuropathological results not only support the MS diagnosis, but provide further evidence that Lewy body pathology may be absent even in homozygote carriers.